Mortality of interhospital transfers originating from an Emergency Department in Perth, Western Australia - Gillman, Lucia; Fatovich, D.; Jacobs, Ian (Elsevier, 2013)
Background: Interhospital transfer (IHT) is an integral part of emergency practice and required to access specialist care. Aim: To identify factors that predict in-hospital mortality for IHT originating from an Emergency Department (ED). Method: A retrospective cohort study utilising linked health data from the ED Information System database, Death Register and the Hospital Morbidity Data examined all IHTs originating from a public hospital ED and transferred to a tertiary hospital ED (ED-ED IHT), January 1st 2002-December 31st 2006. Results: There were 27,776 ED-ED IHTs. In-hospital mortality was 2.1% (95% CI 1.9-2.3%). Age, male sex, clinical deterioration by one or =2 levels on the Australasian Triage Scale (ATS) and circulatory or respiratory disease increased risk of mortality. Clinical improvement by one level on the ATS, injury or poisoning, digestive disease, transfer from 2004 to 2006 and exposure to access block reduced risk of mortality. Other than year of transfer, injury or poisoning, digestive and respiratory disease, these factors were also predictive of mortality within 1-day of transfer. Conclusion: Multiple factors influence mortality following IHT from an ED. Awareness of these factors helps to optimise risk reduction. The limited infrastructure and resourcing available in non-tertiary hospitals are important considerations.